(3habG ddeYGjjQ GdOhdjI ddEHdGZ GdeGdj (BIFRS (3GdfXGe GdeMGSHj GdeGdj (B& SCFs - (3TYjH(B, (3Tfhas ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2016)
(3jJfGhd gPG GdcJGH GdeMGSHI GdeGdjI WHbG ddeYGjjQ GdOhdjI ddEHdGZ GdeGdj hGdfXGe GdeMGSHj GdeGdj hgh YHGQI Yf OQGSI ebGQHI ddeYGdLI GdeMGSHjI Hjf GdeQLYjI GdOhdjI ddeMGSHI hGdeJeKdI aj GdeYGjjQ GdeMGSHjI GdOhdjI heYGjjQ GdGHdGZ GdeGdj GdOhdjI hGdfXGe GdeMGSHj GdLRGFQj , Je JbOjeg hab HQfGeL GdJchjf HejOGf GdYdhe GdEbJUGOjI , GdJSjjQ hGdYdhe GdJLGQjI dfXGe GddjSGfS eGSJQ OcJhQGg, hgh jTed YOOG ef GdaUhd GdeJSdSdI , GdaUd GdChd JfGhd GdeMGSHI GdeGdjI , GdKGfj GdeMGSHI GdeGdjI GdeJbOeI hjJVef GdeMGSHI GdeYebI, GdKGdK GdeYGjjQ GdeMGSHjI GdOhdjI , GdQGHY eYGjjQ GdGHdGZ GdeGdj GdOhdjI, CeG GdaUd GdNGeS aJfGhd BKGQ JHfj hJWHjb GdeYGjjQ GdeMGSHjI GdOhdjI Ydi GdJMdjd GdeGdj(B.s
(3GdeQGLY U(B.359 (3GdedGMb U(B.363s
Keywords: (3GdEHdGZ GdeGdj (B- IFRS s; (3GdeMGSHI GdJMdjdjIs; (3GdfXGe GdeMGSHj GdeGdj (B- SCF s